2019
DOI: 10.3390/ma12020295
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Degradation of Absorbable Zinc Alloys in Artificial Urine

Abstract: Absorbable metals have potential for making in-demand rigid temporary stents for the treatment of urinary tract obstruction, where polymers have reached their limits. In this work, in vitro degradation behavior of absorbable zinc alloys in artificial urine was studied using electrochemical methods and advanced surface characterization techniques with a comparison to a magnesium alloy. The results showed that pure zinc and its alloys (Zn–0.5Mg, Zn–1Mg, Zn–0.5Al) exhibited slower corrosion than pure magnesium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 48 publications
1
19
1
Order By: Relevance
“…The viability of urothelial cells exposed to pure zinc remained high for all incubation times (Figure 2a). In artificial urine solution, magnesium corroded faster than zinc and iron (Figure 2b), confirming the previously published results [24]. The constant trend of the cell viability exposed to zinc could be related to the constant release of Zn 2+ ions into the solution throughout the metal incubation period.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The viability of urothelial cells exposed to pure zinc remained high for all incubation times (Figure 2a). In artificial urine solution, magnesium corroded faster than zinc and iron (Figure 2b), confirming the previously published results [24]. The constant trend of the cell viability exposed to zinc could be related to the constant release of Zn 2+ ions into the solution throughout the metal incubation period.…”
Section: Resultssupporting
confidence: 90%
“…This study began with a preliminary screening step involving a cell viability test and an electrochemical corrosion test on the three classes of absorbable metals: pure iron, magnesium, and zinc, before then focusing on selected zinc alloys. The first screening tests included a water soluble tetrazolium (WST) mitochondrial assay to assess the cell viability of urothelial cells treated for 3 days with the metal extracts, and a potentiodynamic polarization test to determine the corrosion rate in artificial urine solution, as detailed in another work [24]. The second screening test involved a further cell viability test with the addition of two zinc alloys (Zn–1Mg and Zn–0.5Al) and one magnesium alloy (Mg–2Zn–1Mn, or ZM21), which were prepared via casting and extrusion, as detailed in Mostaed et al [23].…”
Section: Methodsmentioning
confidence: 99%
“…In our results, the Zn-Ag-Au-V alloy showed a relatively low degradation rate of 7.34 ± 0.64 µm/year, which was far lower than reported for most Zn-based alloys [2,45]. One explanation might be the high concentration of HPO 4 2in the DPBS (4.2 mM), as listed in Table 1.…”
Section: In Vitro Degradation Behaviorcontrasting
confidence: 58%
“…However, in both cases the CR of Zn-5Ge was much lower than that of pure Zn. Champagne et al [ 273 ] compared the electrochemical CR of HE pure Zn, Zn-0.5Al and Zn-0.5 Mg in AU, and reported that the CR of both alloys was decreased compared to Zn counterparts, but the CR of Zn-0.5 Mg was superior than that of Zn-0.5Al alloy. For Zn based ternary alloys, Bakhsheshi-Rad et al [ 136 ] observed that the addition of Mg (0.1–0.5) progressively increased the CR of Zn-0.5Al ( Table 6 ).…”
Section: Corrosion Mechanisms and Degradation Behaviors Of Pure Zn Anmentioning
confidence: 99%